Relationship between spirituality, nature connectedness, and burnout of schoolteachers during online classes amid Covid-19 pandemic: the moderating role of gender - Tengku Mohamed, Tengku Farhanan; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Ahrari, Seyedali (Society for Research and Knowledge Management, 2022)
The substantial changes in the workplace caused by the Covid-19 pandemic restrictions have contributed to teacher burnout. The purpose of this study was to gain an understanding of the relationships between spirituality, connectedness to nature, and burnout in schoolteachers, as well as to investigate the mediating part of spirituality in the relationship between connectedness to nature and burnout, and the moderating role of gender. This study was conducted using a quantitative method, with a sample size of 123 schoolteachers in Malaysia. Data analysis using partial least squares-structural equation modeling (PLS-SEM) revealed that schoolteachers who had a strong connection to nature were less likely to experience burnout. Spirituality acted as a buffer in the relationship between connection to nature and burnout. The results also differed according to gender for the nature connectedness-burnout relationship. Going forward, the findings of this study offer practitioners better insights about the importance of selected factors, including nature concreteness and spirituality as a promising avenue for reducing burnout among schoolteachers during online classes amid the Covid-19 pandemic.